POLICY DEVELOPMENT OF THE PHUKET WOMEN EMPOWERMENT FUNDS - Hokul , Amporn; Siripornwut, Nuttawat (Journal of MCU Nakhondhat, 2023)
The purposes of this research were: (1) to study the operational conditions of the Phuket Women Empowerment Fund (2) to study the problems and obstacles policy driving Implementation of the policy and (3) to be a guideline for policy formulation the development of the Phuket Women Empowerment Fund. The research model is qualitative research with 25 key informants, observation structured was in-depth interviews data analysis by inductive analysis and analyzed by data type classification. The research results found that: Policy Implementation of Phuket Women's Empowerment Fund Policy Since the policy setting process Policy implementation, control, monitoring, and evaluation have not been successful not as efficient as it should be. And another important factor is public relations communication about the operation of the Phuket Women Empowerment Fund.Guidelines for policy formulation and fund development include the creation of a variety of communication and public relations channels to achieve the same understanding, allow the public to participate encourage women members to have roles in managing the fund. Participate in every step of the implementation of the Women Empowerment Fund. Opening of the additional manpower rate framework and building a network of members of the Phuket Women Empowerment Fund.